The Effect of Transfusion and Hypoxia on Cells in an in vitro Model of the Neurovascular Unit - A. A. Ivkin; E. V. Grigoriev; E. D. Khilazheva; A. V. Morgun (Общая реаниматология, 2024)
Up to 57% of patients develop postoperative delirium after surgery for congenital heart defects (CHD). To reduce cerebral damage in pediatric patients during CHD surgery it is important to find out what inflicts the worse damage: would it be a systemic inflammatory response (SIR) triggered by transfusion, or hypoxia developed in non-transfused patients? In vitro evaluation of hypoxia and SIR effects on the neurovascular unit (NVU) cells might contribute to finding the answer.The aim of the study was to compare the effect of varying severity hypoxia and SIR on the functional activity of NUV cells in vitro.Materials and methods. An in vitro NVU model was designed including neurons, astrocytes and endotheliocytes. The effect of hypoxia on NVU was evaluated in the control (C) and 4 study groups (H 1–4), formed based on O₂ content in the medium. The C group NVU were cultivated in standard conditions: N₂ — 75%, O₂ — 20%, CO₂ — 5%; H1: N₂ — 99%, O₂ — 1%; H2: N₂ — 98%, O₂ — 2%; H3: N₂ — 97%, O₂ — 3%; H4: N₂ — 96%, O₂ — 4%. The significance of the differences was 0.0125. The effect of interleukin-6 (IL-6) content on NVU was measured by adding to culture medium pediatric patients’ serum with known minimal or maximal SIRS-response. The assessment was made in the Control — an intact NVU model, and 2 study groups — «Minimum» and «Maximum», i. e. samples with minimum or maximum IL-6 content in culture, respectively. The significance of the differences was 0.017. The cells were incubated at a normothermia regimen for 30 minutes. Then, the functional activity of NVU cells was evaluated by measuring transendothelial resistance (TER) for 24 hours and Lucifer Yellow (LY) permeability test at 60 and 90 minutes after the start of the experiment.Results. After incubation under hypoxic conditions, TER changes occurred in all studied groups. However, they were statistically significant only in the group with 1% oxygen content in the medium. TER decrease in this group was observed after 2, 4 and 24 hours. LY permeability also changed at 60 and 90 minutes, similarly — in NVU cultivated with 1% oxygen in the medium. Minimal TER values were documented at 4 hours after patients’ serum was added to NVU cells culture medium, and TER increased at 24 hours in both study groups. Cellular permeability to LY changed significantly after 1 hour exposure in both groups — with minimum and maximum IL-6 content in the medium. Although at 90 minutes, there was no difference between the 3 groups in LY permeability tests.Conclusion. Intensive SIR demonstrated short-term but more deleterious than hypoxia, effect on cells in the NVU model. Hypoxia disrupted functional activity of NUV cells only at 1% O₂ concentration in the medium.